Efficiency with Costly Information: A Reinterpretation of Evidence from Managed Portfolios - Elton, Edwin J.; Gruber, Martin J.; Das, Sanjiv; Hlavka, Matthew (Review of Financial Studies, 1993)
We investigate the informational efficiency of mutual fund performance for the period 1965–84. Results are shown to be sensitive to the measurement of performance chosen. Wefind that returns on S&P stocks, returns on non-S&P stocks, and returns on bonds are significant factors in performance assessment. Once we correct for the impact of non-S&P assets on mutual fund returns, wefind that mutual funds do not earn returns that justify their information acquisition costs. This is consistent with results for prior periods.